Seeds for needs: atlas of crop suitability - Gevel, Jeske M.J, van de; Gellaw, A.; Fadda, Carlo; Zonneveld, M. van (Bioversity International, 2013)
A series of policy briefs bringing together the major results and policy recommendations of the Seeds for Needs project which started in 2009. The project was carried out in collaboration with the Institute of Biodiversity Conservation (IBC) in Ethiopia. The methodology and maps were developed by Maarten van Zonneveld (Associate scientist Diversity Analysis for Conservation and Use). The complete set of maps will be published in the Crop Atlas. This project provides a unique framework for combining an improved understanding of climate change scenarios in Ethiopia and available crop diversity information from a range of sources (including genebanks) with farmers’ own experience, indigenous knowledge and traditional adaptation strategies.